2013
DOI: 10.1088/0957-4484/24/35/355701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size on ferroelectric and magnetic properties of BiFeO3nanopowders

Abstract: The ferroelectric and magnetic behaviour of multiferroic BiFeO₃ nanoparticles has been studied using piezoresponse force microscopy (PFM), Mössbauer spectroscopy and SQUID magnetometry. The results of the PFM studies indicate a decay of the spontaneous polarization with decreasing particle size. Nevertheless, particles with diameter ∼50 nm still manifest ferroelectric behaviour. At the same time these particles are weakly ferromagnetic. The Mössbauer spectroscopy studies prove that the weak ferromagnetic state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
42
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 34 publications
10
42
0
1
Order By: Relevance
“…46,47 Another interpretation of the Ti doping-induced appearance of the spontaneous magnetization in BiFeO 3 was recently proposed by Bernardo et al 23 The interpretation is based on the assumption that the nanograins composing Ti-doped samples are smaller than the spin cycloid wavelength, so each one of these nanograins should have a net magnetic moment and should behave as a ferrimagnet. 23 The effect of non-compensated spins on the magnetic properties of BiFeO 3 was recently studied by Castillo et al 48 The BiFeO 3 nanoparticles with diameter $50 nm were found to possess the remanent magnetization of 0.05 emu/g, i.e., far below the value obtained for the BiFe 0.95 Ti 0.05 O 3 samples (M r ¼ 0.19 emu/g) composed of the structural domains of the same size. 23 Very similar remanent magnetization was reported for the magnetically ordered fraction of the BiFeO 3 nanoparticles with a size distribution ranging from 5 of 40 nm.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…46,47 Another interpretation of the Ti doping-induced appearance of the spontaneous magnetization in BiFeO 3 was recently proposed by Bernardo et al 23 The interpretation is based on the assumption that the nanograins composing Ti-doped samples are smaller than the spin cycloid wavelength, so each one of these nanograins should have a net magnetic moment and should behave as a ferrimagnet. 23 The effect of non-compensated spins on the magnetic properties of BiFeO 3 was recently studied by Castillo et al 48 The BiFeO 3 nanoparticles with diameter $50 nm were found to possess the remanent magnetization of 0.05 emu/g, i.e., far below the value obtained for the BiFe 0.95 Ti 0.05 O 3 samples (M r ¼ 0.19 emu/g) composed of the structural domains of the same size. 23 Very similar remanent magnetization was reported for the magnetically ordered fraction of the BiFeO 3 nanoparticles with a size distribution ranging from 5 of 40 nm.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…The effect of grain size on domain structure, dielectric, and piezoelectric properties in different materials has been extensively studied by Arlt and coworkers [60,106,107,108]. Castillo et al [109] revealed that a decrease of the grain size in pure BFO ceramics led to an increase in the elementary cell volume and a decrease of the local piezoresponse. Grains with size below a few hundred nanometers are predominantly single domain [109].…”
Section: Domain Structure In Bifeo3mentioning
confidence: 99%
“…As one of the first publications on the model multiferroic system BiFeO 3 , Blaauw et al found evidence for a complex magnetic structure by a distribution of hyperfine magnetic fields and suspected the existence of several spin orientations with different angles relative to the crystal lattice [196]. Later works indicated cycloidal ordering of spins in BiFeO 3 bulk as well as in nanoparticles using nuclear magnetic resonance and Mössbauer spectroscopy, explaining it by magnetoelectric coupling [197][198][199][200]. In magnetically coupled components of binary magnetoelectric composites, Mössbauer spectroscopy is able to provide information on the type of coupling, the coordination number and valence state of the iron ions and their distribution on different lattice sites, which has major influence on the type of magnetism.…”
Section: Mössbauer-spectroscopymentioning
confidence: 99%